Reliability Of Rapid Penang Operation In Mixed Traffic Situation - Paid, Norazilah Mohamed (Universiti Sains Malaysia, 2017)
Public transportation system has been serving the public user for many years all over the world with variety of public mode available; such as taxi, railway, and public bus transportation system is one of the mode options. The availability of public bus transportation system in most of the countries has gained trusted and confidence from the public user for its quality of service in every aspect such as punctuality, frequency, comfortability and many more. In action to that, the government and related agency have taken responsibility to maintain and increase the quality of service of public bus transportation system for the sake of public user’s prosperity and safety, which uses this public mode as their preferred choice for commuter trip to go anywhere they desired. In this study, Rapid Penang is the focus of the research as to evaluate the performance of public bus transportation system in Penang Island. Northeast Penang Island district is the selected study area as having the higher population and there are three bus routes selected in this district which are bus route 101 for the northern zone, bus route 203 for central zone and bus route 301 for southern zone based on most frequent bus routes. From the results obtained, Rapid Penang has managed to provide good services. Bus route 203 has achieved level of service of A during peak hours and non-peak hours. Meanwhile, bus routes 101 and 301 have achieved level of service of A during morning peak hours and non-peak hours but level of service of B during evening peak hours. Thus, it is important to keep and maintain the performance of public bus transportation system.